Sonographic Evaluation of Incidental Synchronous Masses in Patients with Breast Cancer: Clinical Significance and Diagnostic Workup - Sara Rehman; Imran Khalid Niazi; Muhammad Atif Naveed; Ainy Javaid; Bushra Rehman (European Journal of Breast Health, 2021)

(untitled)
Objective:This study aimed to evaluate the diagnostic accuracy of breast ultrasonography in classifying incidental satellite masses as benign or malignant in patients with breast cancer and to assess its effect on their surgical management.Materials and Methods:Ultrasound-guided fine needle aspiration/biopsy was performed in 288 satellite masses of 225 patients with breast cancer. Two radiologists retrospectively reviewed the sonograms of these masses and classified them as benign or malignant and compared this feature with the results of the histopathological examination. The location of the satellite mass and type of surgery were also documented.Results:Of the 288 satellite masses, 139 were located in the same quadrant, 95 in different quadrants, while 54 were in the contralateral breast. Of the 123 sonographically benign masses, 106 showed benign pathological outcome, and from 165 sonographically malignant masses, 127 were found malignant on histopathology/cytology. McNemar’s chi-square was 7.27 (p-value=0.007), showing statistically significant association between sonographic features and pathological outcome of satellite masses. The sensitivity, specificity, positive and negative predictive values, and accuracy were 88.2%, 73.6%, 77%, 86.1%, and 80.9% respectively. Based on these findings, 61 patients underwent lumpectomy limited to a single tumor, 52 underwent extended resection, 78 underwent mastectomy, four underwent lumpectomy for the contralateral breast, and bilateral mastectomies were performed in another four patients. Surgery was not performed in 26 patients.Conclusion:Although ultrasound is an effective tool for the detection and characterization of incidental satellite masses in patients with breast cancer, biopsy is imperative to ascertain the pathological diagnosis and, therefore, select the most appropriate surgical plan.